Ferrite composition and magnetic core comprising same

By optimizing the composition of magnetic ionic agents and non-magnetic additives, a ferrite composition is designed to solve the problem of a large loss increase rate of existing magnetic cores under different temperature environments, and the minimum loss increase rate of minimized loss and loss increase rate is achieved, which improves the reliability and stability of the equipment.

CN119522461APending Publication Date: 2025-02-25LG INNOTEK CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047998.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-05-09
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing magnetic core has a large loss increase rate under different temperature environments, resulting in an increase in energy loss and an increase in heat dissipation demand, which in turn affects the reliability of equipment and the stability of peripheral components.

Method used

By optimizing the composition of the magnetic ionic agent, the composition of the main components and the amount of non-magnetic additives, a ferrite composition is designed, which maintains the core loss at 100 kHz and 200 mT at 300 mW/cc or less in the range of 80°C to 100°C, and maintains the coercive force and core loss change rate within a reasonable range from 25°C to 140°C.

Benefits of technology

Minimized minimum loss and minimized loss increase rate with temperature change are achieved, reducing energy loss and heat generation of the core, improving the reliability of the equipment and the stability of the peripheral components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522461A_ABST
    Figure CN119522461A_ABST
Patent Text Reader

Abstract

The magnetic core according to the present invention comprises: main components including a manganese (Mn) component having an atomic ratio in the range of 0.74 to 0.76, a zinc (Zn) component having an atomic ratio in the range of 0.15 to 0.17, an iron (Fe) component having an atomic ratio in the range of 2.08 to 2.09, and a cobalt (Co) component having an atomic ratio in the range of 0.005 to 0.010; a magnetic ionic agent; and a non-magnetic additive, in which a magnetic core loss of the magnetic core at 80 DEG C to 100 DEG C is 300 mW / cc or less under conditions of a frequency of 100 kHz and a maximum magnetic flux density of 200 mT.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ferrite composition and a magnetic core including the ferrite composition, wherein the ferrite composition has a minimized minimum loss and a minimized loss increase rate with temperature change. Background Art

[0002] Ongoing environmental issues and regulations have recently prompted the development of cores for magnetic components that can be used over a wide operating temperature range, and the market for cores for such magnetic components is expanding. As a result, the importance of power components in fields ranging from televisions to electronics is increasing.

[0003] Generally speaking, the magnetic cores that make up inductors or transformers have problems with meeting the reliability requirements of the surrounding environment, such as low-temperature characteristics or thermal shock.

[0004] Power components and modules with magnetic cores consisting of inductors or transformers may experience increased energy losses depending on the operating environment of the power components and modules. In this case, the operating environment may mean that component heat generation gradually increases as the temperature rises within the operating temperature range when the module is operating. Therefore, to compensate for this, higher energy may be required for component heat dissipation and cooling.

[0005] Furthermore, power components and modules using magnetic cores may cause malfunction and damage to peripheral components (TFTs) due to heat generation, thereby reducing power consumption of next-generation platforms such as EVs that use electricity as a main power source.

[0006] Therefore, it is necessary to consider a method to reduce the heat generation while reducing the core loss. Summary of the invention

[0007]

Technical issues

[0008] Embodiments of the present invention provide a ferrite composition having minimized lowest loss and minimized loss increase rate with temperature change, and a magnetic core including the same.

[0009] Specifically, embodiments of the present invention provide a ferrite composition having minimized lowest loss and minimized loss increase rate with temperature by optimizing the composition of the magnetic ion agent, the composition of the main component, and the amount of the added non-magnetic additive.

[0010] The technical problems to be solved by the embodiments of the present invention are not limited to the above-mentioned technical problems, and other technical problems not mentioned herein will be clearly understood by technicians in the field to which the embodiments of the present invention belong from the following description.

[0011]

Technical solution

[0012] A magnetic core according to an embodiment of the present invention may include: a main component comprising a manganese (Mn) component with an atomic ratio of 0.74 to 0.76, a zinc (Zn) component with an atomic ratio of 0.15 to 0.17, an iron (Fe) component with an atomic ratio of 2.08 to 2.09, and a cobalt (Co) component with an atomic ratio of 0.005 to 0.010; a magnetic ion agent and a non-magnetic additive, wherein at a frequency of 100 kHz and a maximum magnetic flux density of 200 mT, the magnetic core has a core loss of 300 mW / cc or less at 80°C to 100°C.

[0013] In one embodiment, the magnetic core may have a coercivity variation rate of -7% to 20% at 25°C to 140°C.

[0014] In one embodiment, the core loss variation rate may be -6% to 18% at 25°C to 140°C.

[0015] In one embodiment, the magnetic core may have a core loss variation value of less than 100 mW / cc at 25°C to 140°C.

[0016] In one embodiment, the core loss variation value of the magnetic core may be in the range of 60 mW / cc to 99 mW / cc.

[0017] In one embodiment, the magnetic core may have an initial magnetic permeability of 3000 or more.

[0018] In one embodiment, the magnetic core may have an atomic ratio of a manganese (Mn) component / zinc (Zn) component in the range of 4.40 to 4.60.

[0019] In one embodiment, the magnetic ionic agent may include a compound of iron (Fe) and a compound of cobalt (Co) (Fe+Co).

[0020] In one embodiment, in the magnetic ionic agent, an atomic ratio of the compound of iron (Fe) to the compound of cobalt (Co) (Fe+Co) may be in the range of 2.08 to 2.10.

[0021] In one embodiment, in the main component, an atomic ratio of the cobalt (Co) component with respect to the total atoms of the main component may be in the range of 0.005 to 0.01.

[0022] In one embodiment, the non-magnetic additive may include at least one of calcium oxide (CaO), niobium oxide (Nb2O5), or a mixture thereof.

[0023] The content of calcium oxide (CaO) may be 400 ppm to 600 ppm.

[0024] The content of niobium oxide (Nb2O5) may be 50ppm to 600ppm.

[0025] In addition, the magnetic core may include 21.2wt% to 21.6wt% of manganese oxide (MnO) containing a manganese component, 5.7wt% to 6.1wt% of zinc oxide (ZnO) containing a zinc component, 72wt% to 72.7wt% of iron oxide (Fe2O3) containing an iron component, and 0.3wt% to 0.4wt% of cobalt oxide (Co3O4) containing a cobalt component.

[0026]

Beneficial Effects

[0027] According to an embodiment of the present invention, by optimizing the composition of the magnetic ion agent, the composition of the main component and the composition of the non-magnetic additive, the ferrite composition and the magnetic core including the ferrite composition can minimize the minimum loss of the magnetic core and minimize the loss increase rate with temperature.

[0028] Effects obtainable from the embodiments of the present invention are not limited to the above-mentioned effects, and other effects not mentioned can be clearly understood by those skilled in the art from the following description.

[0029] BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a block diagram showing the configuration of a ferrite composition and a magnetic core including the ferrite composition according to one embodiment.

[0031] Figure 2 is a set of graphs showing the relationship between the variation of core loss with temperature and the atomic ratio of magnetic ionic agents (Fe+Co) in a magnetic core formed from a ferrite composition according to one embodiment.

[0032] Figure 3 is a set of graphs showing the relationship between core loss as a function of temperature and manganese (Mn) / zinc (Zn) atomic ratio in a magnetic core formed from a ferrite composition according to one embodiment.

[0033] Figure 4 is a set of graphs showing the relationship between the amount of non-magnetic additive added and the change in core loss in the magnetic core of Sample 9 formed of a ferrite composition according to one embodiment.

[0034] Figure 5 is a set of graphs showing the relationship between the amount of non-magnetic additive added and the change in magnetic permeability in the magnetic core of Sample 9 formed of a ferrite composition according to one embodiment.

[0035] Figure 6is a set of graphs showing coercive force and core loss measured in Sample 15 formed of a ferrite composition according to one embodiment.

[0036] Figure 7 is a set of graphs showing a comparison of core losses in a magnetic core of Sample 15 formed from a ferrite composition and a commercially available magnetic core component according to one embodiment.

[0037] Best Practice Implementation Details

[0038] The present invention can be modified in various ways and can be implemented in various ways, which will be described in detail with reference to the accompanying drawings. However, the present invention should not be interpreted as being limited to a specific embodiment, but should be understood to include all modifications, equivalents or substitutes falling within the concept and technical scope of the present invention.

[0039] It should be understood that although terms including ordinal numbers (such as "second" or "first") may be used herein to describe various elements, these elements are not limited to these terms, which are only used to distinguish one element from another element. For example, without departing from the scope of protection of the present invention, the second element can be named as the first element, and similarly, the first element can be named as the second element. The term "and / or" includes a combination of multiple associated items, or any one of multiple associated items.

[0040] When it is mentioned that a certain element is "connected to" or "connected to" another element, it should be understood that the element may be directly connected to or connected to another element, or there may be one or more other elements as intermediaries. On the other hand, when it is mentioned that a certain element is "directly connected to" or "directly connected to" another element, it should be understood that there are no other elements intervening.

[0041] It should be understood that when an element, such as a layer (film), region, pattern or structure is referred to as being "on" or "below" another element, such as a substrate, layer (film), region, pad or pattern, it may be directly above or below the element, or one or more intermediate elements may be present therebetween. When an element is referred to as being "above" or "below", both "below the element" and "above the element" may be included depending on the element itself. In addition, in the drawings, for clarity and convenience, the thickness or size of the layer (film), region, pattern or structure may be exaggerated and therefore may be different from their actual thickness or size.

[0042] In addition, the terms used herein are only used to illustrate certain embodiments and should not be interpreted as limiting the scope of the present invention. Singular forms are intended to also include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "including" and / or "having" used herein specify the presence of the features, numbers, steps, operations, elements, components or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, operations, elements, components or combinations thereof.

[0043] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by those skilled in the art. In addition, terms that are the same as those defined in commonly used dictionaries should be interpreted as having the same meaning as the contextual meaning in the relevant technology, and should not be interpreted as having an unusual or overly formal meaning unless explicitly defined herein.

[0044] One embodiment of the present invention provides a ferrite composition having an optimized design to produce the lowest loss and minimize the loss variation depending on temperature variation to form a magnetic product maintaining low loss characteristics.

[0045] Figure 1 is a block diagram illustrating the configuration of a ferrite composition and a magnetic core including the ferrite composition according to one embodiment of the present invention.

[0046] Reference Figure 1 The ferrite composition C according to one embodiment of the present invention includes a main component C1, a magnetic ion agent C2, and a non-magnetic additive C3. In the present embodiment, the magnetic core 10 is described as an example of a magnetic product formed using the ferrite composition C.

[0047] The main component C1 may include a manganese (Mn) component, a zinc (Zn) component, an iron (Fe) component, and a cobalt (Co) component.

[0048] The magnetic ion agent C2 may include both a compound of iron (Fe) and a compound of cobalt (Co) that form magnetic ions. 2+ , Fe 3+ and Co 2+ The magnetic ions are transferred to the magnetic core 10 .

[0049] The non-magnetic additive C3 can minimize the coercivity that varies with temperature. The non-magnetic additive C3 can include at least one of calcium oxide (CaO), niobium oxide (Nb2O5), or a mixture thereof.

[0050] According to one embodiment, the ferrite composition C constituting the magnetic core 10 may be designed to induce the lowest loss of the magnetic core 10 based on controlling the composition of the magnetic ion agent C2 and the main component C1.

[0051] By optimizing the content of the magnetic ionic agent C2, the magnetic core 10 with low coercivity can be formed by inducing the lowest loss (Pcv). The coercivity may affect the hysteresis loss. In addition, the coercivity may be affected by the magnetic ionic agent C2.

[0052] In order to form the magnetic core 10 having a low coercive force, 7 starting materials were prepared under conditions 1 to 7, as shown in Table 1 below.

[0053] [Table 1]

[0054]

[0055]

[0056] Table 1 shows the atomic ratio and content ratio of the starting materials for preparing the magnetic core samples. The starting materials prepared as shown in Table 1 do not include the non-magnetic additive C3.

[0057] As shown in Table 1, as a component of the main component C1, the atomic ratio of cobalt (Co) can be added in the range of 0.010 to 0.020. Herein, the atomic and content ratio of manganese (Mn), zinc (Zn) and iron (Fe) constituting the main component C1 are adjusted under the condition that the atomic weight ratio of cobalt (Co) is fixed to 0.015. In addition, as the magnetic ion agent C2, the atomic ratio of the iron (Fe) compound and the cobalt (Co) compound is set in the range of 2.06 to 2.14.

[0058] The contents of the main component C1 and the magnetic ion agent C2 can be analyzed by a WD-XRF (wavelength dispersive X-ray fluorescence) apparatus as follows.

[0059] [Table 2]

[0060]

[0061] As shown in the results of WD-XRF analysis in Table 2, the content of each raw material is consistent with that of the ferrite composition C in Table 1, but the content of the magnetic core 10 changes due to certain reasons, such as powder loss, that is, combustion loss may occur during the production of the magnetic core 10 using the ferrite composition C.

[0062] Table 2 shows the content ratios of the raw materials constituting the samples of the magnetic core 10 produced using the ferrite composition C under conditions 1 to 7 in Table 1.

[0063] Manganese (Mn), zinc (Zn), iron (Fe) and cobalt (Co) constituting the main component C1 are raw materials in the form of oxides. In addition, the magnetic ion agent C2 can also be prepared from iron oxide (Fe2O3) and cobalt oxide (Co3O4).

[0064] For example, samples 1 to 7 of the magnetic core 10 formed with the raw material content ratio of the ferrite composition C shown in Table 1 contain 19.54wt% to 21.34wt% of manganese oxide (MnO), 6.70wt% to 7.35wt% of zinc oxide (ZnO), 71.05wt% to 73.22wt% of iron oxide (Fe2O3), and 0.49wt% to 0.54wt% of cobalt oxide (Co3O4).

[0065] Figure 2 is a set of graphs showing the relationship between the core loss as a function of temperature and the atomic ratio of magnetic ionic agents (Fe+Co) in each magnetic core formed from a ferrite composition according to one embodiment.

[0066] Figure 2 The graph shows the lowest loss of the measured magnetic core 10 sample, which is prepared under 7 conditions, wherein the atomic ratio of the manganese (Mn) component / zinc (Zn) component in the main component (C1) is set to 3.35 to 3.65, and the atomic ratio of the iron (Fe) compound and the cobalt (Co) compound (Fe+Co) is set to 2.06 to 2.14.

[0067] Here, the magnetic core 10 samples 1 to 7 in Table 2 were manufactured according to Conditions 1 to 7 shown in Table 1, the magnetic core 10 samples were wound with 10 primary coils and 10 secondary coils, and the core loss of the magnetic core (10) wound with the primary and secondary coils as above was measured at a frequency of 100 kHz and a maximum magnetic flux density of 200 mT.

[0068] like Figure 2 As shown, the minimum loss of samples 1 to 6 drops from 2214 mW / cc to 589 mW / cc at -30°C to 140°C. The minimum loss of sample 6 at room temperature (27°C) is 589 mW / cc, while the minimum loss of sample 1 at 140°C is 2214 mW / cc.

[0069] Among these samples, as the atomic ratio of iron (Fe) and cobalt (Co) compounds (Fe+Co) decreases, the core loss of samples 4 to 6 decreases compared to samples 1 to 3.

[0070] Specifically, compared with samples 1 to 3 using an atomic ratio of iron (Fe) compounds and cobalt (Co) compounds (Fe+Co) of 2.11 to 2.14, the loss of samples 4 to 6 using an atomic ratio of iron (Fe) compounds and cobalt (Co) compounds (Fe+Co) of 2.07 to 2.10 was reduced.

[0071] On the other hand, in Table 2, the overall core loss of Sample 7 is lower, but it is not considered useful because it is difficult for Sample 7 to have the lowest loss, mainly because of the difference between the core loss variation graph and the coercive force variation graph.

[0072] Therefore, when the atomic ratio of both the iron (Fe) compound and the cobalt (Co) compound (Fe+Co), that is, the atomic ratio as the magnetic ion agent C2, is within the range of 2.07 to 2.10, it is found that the core loss is lower.

[0073] This is because the coercivity of the sample may be minimized by controlling the content of the magnetic ionic agent C2. In other words, the induced coercivity level can be obtained by the width of the hysteresis loop, while the increase in core loss (Pcv) may be very sensitive to the changes in hysteresis loss (Phv) and eddy current loss (Pev).

[0074] Therefore, it can be seen that the Fe in the magnetic ion agent C2 2+ , Fe 3+ and Co 2+ The magnetic ions may minimize the coercivity of the magnetic core 10. In other words, the cobalt (Co) component may replace the iron ions (Fe 2+ ), thereby improving the temperature dependence and helping to control the magnetic anisotropy.

[0075] Therefore, according to one embodiment, the ferrite composition C and the magnetic core 10 including the ferrite composition C may exhibit similar coercive force changes and core loss changes when the temperature changes, and the loss of the magnetic core 10 may be reduced and the changes caused by temperature changes may be minimized by controlling the content of the magnetic ion agent C2.

[0076] Meanwhile, according to one embodiment, the core loss of the ferrite composition C and the magnetic core 10 including the ferrite composition C may also be minimized by controlling the mixing ratio of the iron (Fe) and cobalt (Co) components.

[0077] According to one embodiment, the optimal mixing ratio of iron (Fe) and cobalt (Co) is to minimize the core loss of the ferrite composition C and the magnetic core 10 including the ferrite composition C, as shown in Table 3 below.

[0078] [Table 3]

[0079]

[0080]

[0081] As shown in Table 3, in the ferrite composition C, the manganese (Mn) component is added at an atomic ratio of 0.73 to 0.76, and preferably at an atomic ratio of 0.74 to 0.76.

[0082] In the ferrite composition C, the zinc (Zn) component is added at an atomic ratio of 0.15 to 0.18, and preferably at an atomic ratio of 0.15 to 0.16.

[0083] In the ferrite composition C, the iron (Fe) component is added at an atomic ratio of 2.07 to 2.08, and preferably at an atomic ratio of 2.08.

[0084] In the ferrite composition C, the cobalt (Co) component was added at an atomic ratio of 0.01.

[0085] exist Figure 3 In samples 4 to 6 having the lowest loss, the atomic ratio of the magnetic ion agent C2 of samples 4 and 5 was set to 2.10 and 2.08 based on the total atomic ratio of the main component C1, and the atomic ratio of the cobalt (Co) component was set to 0.01.

[0086] In addition, the atomic ratio of manganese (Mn) / zinc (Zn) is set to a range of 4.0 to 5.0.

[0087] [Table 4]

[0088]

[0089] Table 4 shows the WD-XRF analysis results of the raw material content ratio of the magnetic core 10 samples formed with the ferrite composition C under conditions 8 to 12 of the atomic ratio and the raw material content ratio shown in Table 3.

[0090] As shown in Table 4, manganese (Mn), zinc (Zn), iron (Fe) and cobalt (Co) components constituting the main component C1 are used in the form of oxides, iron oxide (Fe2O3) and cobalt oxide (Co3O4) constituting the magnetic ion agent C2 are used in the form of oxides, and the optimized ratio of the iron (Fe) compound and the cobalt (Co) compound (Fe+Co) is measured.

[0091] For example, the magnetic core 10 samples 8 to 12 formed with the raw material content ratio of the ferrite composition C shown in Table 3 contain 20.38wt% to 21.92wt% of manganese oxide (MnO), 5.55wt% to 6.62wt% of zinc oxide (ZnO), 71.78wt% to 73.55wt% of iron oxide (Fe2O3) and 0.35wt% to 0.36wt% of cobalt oxide (Co3O4).

[0092] Figure 3 is a set of graphs showing the relationship between core loss and temperature at different manganese (Mn) / zinc (Zn) atomic ratios in a magnetic core formed from a ferrite composition according to one embodiment.

[0093] Figure 3 The lowest loss of the prepared magnetic core 10 sample measured is shown, in which the atomic ratio of the compound (Fe+Co) of iron (Fe) and cobalt (Co) constituting the magnetic ion agent C2 in the main component C1 is set to 2.10 to 2.08, and the atomic ratio of the manganese (Mn) component / zinc (Zn) component is set to 4.0 to 5.0.

[0094] Here, if Figure 3 As shown in the chart, Figure 2 The manufactured magnetic core 10 sample shown was wound with 10 primary coils and 10 secondary coils, and the core loss of the magnetic core 10 sample wound with the primary coils and the secondary coils as above was measured at a maximum magnetic flux density of 200 mT and a frequency of 100 kHz.

[0095] like Figure 3 As shown, the lowest loss of samples 8 to 12 is 550 mW / cc to 390 mW / cc at -30°C to 140°C. In particular, the lowest loss of sample 9 at 80°C is 419 mW / cc, while the lowest loss of sample 8 at 40°C is 390 mW / cc.

[0096] Among these samples, samples 8 and 9 have the lowest core loss under the condition that the atomic ratio of the iron (Fe) compound and the cobalt (Co) compound (Fe+Co) is 2.10, and the lowest core loss is lower than the core loss under the condition that the atomic ratio of the iron (Fe) compound and the cobalt (Co) compound (Fe+Co) is 2.08.

[0097] Therefore, when the atomic ratio of (Fe+Co) of the compound of iron (Fe) and the compound of cobalt (Co) is in the range of 2.08 to 2.10, the lowest core loss may be obtained.

[0098] In addition, it can be seen that the lowest loss is obtained when the atomic ratio of manganese (Mn) component / zinc (Zn) component is 4.5 to 5.0. In particular, it can be seen that when the atomic ratio of manganese (Mn) component / zinc (Zn) component is 4.5, the lowest loss is lower at 40°C.

[0099] This is because by controlling the content of iron (Fe) compounds and cobalt (Co) compounds (Fe+Co), as well as controlling the atomic weight ratio of manganese (Mn) component / zinc (Zn) component, the change in hysteresis loss caused by temperature change can be minimized, thereby minimizing the changing trend of core loss.

[0100] Therefore, according to one embodiment, the ferrite composition C and the magnetic core 10 containing the ferrite composition can provide similar temperature-based coercive force change behavior and core loss change behavior, and the loss of the magnetic core 10 can be reduced and the change with temperature can be minimized by controlling the content of iron (Fe) compounds and cobalt (Co) compounds (Fe+Co) and controlling the atomic ratio of manganese (Mn) / zinc (Zn) components.

[0101] Furthermore, by adding the non-magnetic additive C3 in sample 9, the coercivity can be minimized, resulting in the lowest losses.

[0102] The optimal conditions for minimizing the coercivity to produce the lowest loss by the non-magnetic additive C3 are shown in Table 5 below.

[0103] [Table 5]

[0104]

[0105] Table 5 shows the content ratio of the non-magnetic additive C3 based on the atomic ratio of sample 9 in the magnetic core sample. As shown in Table 5, calcium oxide (CaO) and niobium oxide (Nb2O5) are added to the magnetic core 10 as the non-magnetic additive (C3) based on the atomic ratio of sample 9. In the present embodiment, the non-magnetic additive C3 includes both calcium oxide (CaO) and niobium oxide (Nb2O5), but this is not limited to this, and the non-magnetic additive C3 may include at least one of calcium oxide (CaO) or niobium oxide (Nb2O5).

[0106] The non-magnetic additive C3 can reduce the temperature-based core loss of the magnetic core 10. Therefore, the content of the non-magnetic additive C3 is controlled and the resulting change is measured.

[0107] At this time, the ratio of calcium oxide (CaO) added may be set to 400 ppm to 600 ppm.

[0108] [Table 6]

[0109]

[0110] Table 6 shows the WD-XRF analysis results of the raw material content ratio of the magnetic core 10 sample formed of the ferrite composition C under the conditions of the atomic ratio and the raw material content ratio shown in Table 5. Table 6 shows the contents of the main component C1 and the magnetic ion agent C2 of the sample 9 in Table 4, as shown in Table 5, formed by adding 50ppm to 600ppm of niobium oxide (Nb2O5) to form the magnetic core sample.

[0111] As shown in Table 5, niobium oxide (Nb2O5) as the non-magnetic additive C3 was adjusted from 50 ppm to 600 ppm under the varying conditions. On the other hand, as shown in Table 6, the content of the non-magnetic additive C3 may be different from that of the final part due to powder loss (i.e., ignition loss) during the process of manufacturing the samples.

[0112] Samples 13 to 18 of the magnetic core 10 formed with the raw material content ratio of the ferrite composition C shown in Table 6 contain 21.29wt% to 21.57wt% of manganese oxide (MnO), 5.76wt% to 6.06wt% of zinc oxide (ZnO), 72.09wt% to 72.33wt% of iron oxide (Fe2O3) and 0.32wt% to 0.34wt% of cobalt oxide (Co3O4).

[0113] Furthermore, the non-magnetic additive C3 contains 40 ppm to 600 ppm of calcium oxide (CaO) and 50 ppm to 600 ppm of niobium oxide (Nb2O5).

[0114] Figure 4 is a graph showing changes in core loss based on the amount of a non-magnetic additive added to the core of Sample 9 made with a ferrite composition according to one embodiment, Figure 5 is a graph showing changes in magnetic permeability based on the amount of a non-magnetic additive added to the magnetic core of Sample 9 made of a ferrite composition according to an embodiment.

[0115] Here, Figure 4 and Figure 5 The temperature-dependent core loss and temperature-dependent permeability are shown separately.

[0116] Here, the magnetic core 10 sample shown in Table 6 formed of the raw materials shown in Table 5 was wound with 10 primary coils and 10 secondary coils, and the core loss of the magnetic core 10 sample wound with the primary coil and the secondary coil as above was measured at a maximum magnetic flux density of 200mT and a frequency of 100kHz. The results are as follows: Figure 4 and Figure 5 as shown in the chart.

[0117] Figure 4 and Figure 5 The core loss and permeability are shown at temperatures from 25°C to 140°C, respectively.

[0118] See also Figure 4 , Sample 13 has a minimum loss of 363mW / cc at 80℃ and a maximum loss of 506mW / cc at 140℃. Sample 14 has a minimum loss of 354mW / cc at 80℃ and a maximum loss of 450mW / cc at 140℃. Sample 15 has a minimum loss of 296mW / cc at 80℃ and a maximum loss of 379mW / cc at 140℃. Sample 16 has a minimum loss of 355mW / cc at 80℃ and a maximum loss of 396mW / cc at 140℃. Sample 17 has a minimum loss of 368mW / cc at 100℃ and a maximum loss of 451mW / cc at 140℃. Sample 18 has a minimum loss of 368mW / cc at 100℃ and a maximum loss of 440mW / cc at 140℃.

[0119] Therefore, the core losses measured at each temperature are summarized in Table 7 below.

[0120] [Table 7]

[0121]

[0122]

[0123] Referring to Table 7, the loss variation (ΔPcv), which represents the difference between the highest loss and the lowest loss, is 60mW / cc to 143mW / cc. The loss variation of sample 13 is 143mW / cc, the loss variation of sample 14 is 96mW / cc, the loss variation of sample 15 is 83mW / cc, the loss variation of sample 16 is 60mW / cc, the loss variation of sample 17 is 83mW / cc, and the loss variation of sample 18 is 99mW / cc.

[0124] The loss variation represents the difference between the highest loss and the lowest loss and is a parameter of the loss increment. As the loss variation decreases, the loss increment also decreases. A magnetic core 10 having a loss variation of 100 mW / cc or less can be regarded as having a low loss increment.

[0125] As shown in Table 7, except for Sample 13, the loss changes of all Samples 14 to 18 are 100 mW / cc or less, indicating that the loss increment is small. On the other hand, the loss change of Sample 13 is 143 mW / cc, which exceeds 100 mW / cc, indicating that the loss increment is high compared with the other samples. Therefore, the core containing 50 ppm to 500 ppm of niobium oxide (Nb2O5) has a small loss change.

[0126] Therefore, according to one embodiment, with respect to the ferrite composition C and the magnetic core 10 containing the ferrite composition C, samples 14 to 18 have a loss variation of 60 mW / cc to 99 mW / cc in the temperature range of room temperature (25°C) to 140°C, i.e., the loss variation is less than 100 mW / cc, thereby having a minimized loss increment.

[0127] See also Figure 5 According to one embodiment, the ferrite composition C and the magnetic core 10 including the ferrite composition C have a magnetic permeability of 2,651 to 4,540 in a temperature range of room temperature (25° C.) to 140° C. At this time, the magnetic permeability at room temperature (25° C.) may be defined as an initial magnetic permeability.

[0128] According to one embodiment, the measured magnetic permeability data of the ferrite composition and the magnetic core 10 containing the ferrite composition within the temperature range of room temperature (25° C.) to 140° C. are summarized in Table 8 below.

[0129] [Table 8]

[0130]

[0131] Referring to Table 8, the magnetic permeabilities of samples 14 to 18 having the smallest change in loss in Table 7 are 3003 to 4540, while the magnetic permeability of sample 13 is 2651 to 3153. In other words, the magnetic permeabilities of samples 14 to 18 are higher than that of sample 13.

[0132] Therefore, according to one embodiment, regarding the ferrite composition and the magnetic core 10 containing the ferrite composition, samples 14 to 18 have a minimized loss increase of 60mW / cc to 99mW / cc in the temperature range of room temperature (25°C) to 140°C, and have a high magnetic permeability of 3003 to 4540.

[0133] Table 9 summarizes examples of minimizing the core loss according to the content ratio of the magnetic ion agent C2, the content ratio of manganese (Mn) to zinc (Zn), and the non-magnetic additive C3.

[0134] [Table 9]

[0135]

[0136]

[0137] It can be seen that when the content of manganese oxide (MnO) is 21.2wt% to 21.6wt%, the content of zinc oxide (ZnO) is 5.7wt% to 6.1wt%, the content of iron oxide (Fe2O3) is 72wt% to 72.7wt%, the content of cobalt oxide (Co3O4) is 0.3wt% to 0.4wt%, and as the non-magnetic additive C3, the content of calcium oxide (CaO) is 400ppm to 600ppmm, and the content of niobium oxide (Nb2O5) is 50ppm to 600ppm, the minimum loss of the magnetic core is minimized, and the loss increment based on temperature change is also minimized.

[0138] Therefore, according to one embodiment, the magnetic core 10 formed using the ferrite composition C can minimize the loss of the magnetic core 10 and minimize the loss increment based on temperature change by optimizing the addition amount of the non-magnetic additive C3.

[0139] Figure 6 is a set of graphs showing measured coercive force and core loss of a sample 15 formed of a ferrite composition according to one embodiment, Figure 7 is a set of graphs showing a comparison of core losses of a magnetic core of Sample 15 formed from a ferrite composition according to one embodiment with commercially available magnetic core components.

[0140] from Figure 6 It can be seen from the graph that the variation of the core loss with temperature is consistent with the variation of the coercive force of the magnetic core 10 formed with the ferrite composition according to one embodiment.

[0141] According to one embodiment, the coercivity of the magnetic core 10 formed using the ferrite composition may be affected by the magnetic ion agent (Fe 2+ , Fe 3+ and Co 2+ ) content ratio and the influence of the magnetic anisotropy size depending on temperature, as mentioned above Figures 2 to 5 The composition is shown. This coercivity may affect the hysteresis losses.

[0142] Therefore, the coercivity of the magnetic core 10 formed of the ferrite composition can be reduced by optimizing the atomic ratio of the magnetic ion agent (Fe+Co) and the atomic ratio of manganese (Mn) / zinc (Zn). That is, by designing the ferrite composition C with low coercivity, the lowest loss of the magnetic core 10 can be obtained.

[0143] Furthermore, according to one embodiment, by controlling the content of the nonmagnetic additive C3, the coercivity change of the magnetic core 10 formed using the ferrite composition based on temperature change can be minimized while reducing the minimum loss. Magnetic anisotropy depends on temperature, and the degree of magnetic anisotropy may change with temperature change.

[0144] Therefore, controlling the content of the non-magnetic additive C3 may affect the loss change (increment) caused by controlling the temperature change.

[0145] For example, according to one embodiment, the core 10 of sample 15 formed with the ferrite composition has a core loss ranging from 296 mW / cc to 379 mW / cc at 25°C to 140°C, has a lowest core loss of 296 mW / cc at 80°C to 100°C, and has a highest core loss of 379 mW / cc at 140°C.

[0146] Furthermore, according to one embodiment, the magnetic core 10 of the sample 15 formed with the ferrite composition has a coercive force ranging from 4.6 A / m to 6.2 A / m at 25°C to 140°C, a minimum coercive force of 4.6 A / m at 80°C, and a maximum coercive force of 6.2 A / m at 140°C.

[0147] like Figure 6 As shown, the variation law of coercive force and the variation law of core loss are summarized in the following Table 10.

[0148] [Table 10]

[0149] temperature 25℃ 40℃ 60℃ 70℃ 80℃ 100℃ 120℃ 140℃ Coercive force (A / m) 5.5 5.2 4.9 4.7 4.6 4.7 5.2 6.2 Variation of coercivity with temperature -4.6% -6.7% -3.3% -1.9% 1.4% 10.9% 18.2% Core loss (mW / cc) 344 330 310 301 296 296 323 379 Core loss variation with temperature -4.2% -5.9% -2.9% -1.9% 0.1% 9.0% 17.4%

[0150] As shown in Table 10, the core loss variation rate of the magnetic core 10 formed with the ferrite composition according to one embodiment is between -6% and 18%. For example, the magnetic core 10 has a minimum core loss variation rate of -5.9% at 80°C and a maximum core loss variation rate of 17.4% at 140°C.

[0151] In addition, the coercivity variation rate of the magnetic core 10 formed of the ferrite composition according to one embodiment is within a range of -7% to 20%. For example, the magnetic core 10 has a minimum coercivity variation rate of -6.7% at 60°C and a maximum coercivity variation rate of 18.2% at 140°C.

[0152] From the core loss change rate and coercivity change rate Figure 6 It can be seen that the law of the core loss change rate is similar to the law of the coercive force change rate.

[0153] Therefore, it can be seen that in the above Figures 2 to 5 Under the operating conditions described above, the core loss of the magnetic core 10 formed using the ferrite composition according to one embodiment depends largely on the hysteresis loss. It can be seen that when the main factors of the composition design correspond to the purpose, for example, the ferrite composition is optimized to reduce the coercive force as much as possible and its change rate is not large, the change of the hysteresis loss with temperature is minimized, thereby achieving a material with low core loss of the magnetic core 10 and small change with temperature.

[0154] See also Figure 7 , the magnetic core 10 formed using the ferrite composition according to one embodiment has lower core loss than the comparative example.

[0155] According to the present embodiment, the magnetic core 10 has the core loss measured for the sample 15 .

[0156] Compared with Comparative Examples 1 to 5, the core loss of the present embodiment is the lowest. Figure 6 As shown, since the embodiments of the present invention show a core loss change rate law similar to the coercive force change rate, the minimum loss of the core can be minimized and the loss increase rate based on temperature change can be minimized by optimizing the composition of the magnetic ion agent, the composition of the main components and the addition amount of the non-magnetic additives.

[0157] The description of each embodiment is applicable to other embodiments as long as the contents of each embodiment do not conflict with each other.

[0158] Although the present disclosure has been particularly shown and described with reference to its exemplary embodiments, these embodiments are presented for illustrative purposes only and do not limit the present disclosure, and it is apparent to those skilled in the art that various changes in form and detail may be made without departing from the basic features of the embodiments described herein. For example, the various configurations listed in the embodiments of the present invention may be modified and applied. In addition, it should be understood that the differences in such modifications and applications fall within the scope defined by the claims appended to the present disclosure.

[0159] [Industrial Applicability]

[0160] The ferrite composition according to the embodiment of the present invention and the magnetic core including the ferrite composition may be used for power supplies of various electronic products.

Claims

1. A magnetic core, comprising: A main component comprising a manganese (Mn) component in an atomic ratio ranging from 0.74 to 0.76, a zinc (Zn) component in an atomic ratio ranging from 0.15 to 0.17, an iron (Fe) component in an atomic ratio ranging from 2.08 to 2.09, and a cobalt (Co) component in an atomic ratio ranging from 0.005 to 0.010; Magnetic ionizing agents; and Non-magnetic additives, Wherein, at a frequency of 100 kHz and a maximum magnetic flux density of 200 mT, the magnetic core has a core loss of 300 mW / cc or less at 80° C. to 100° C. 2 . The magnetic core according to claim 1 , wherein the magnetic core has a coercivity variation rate of −7% to 20% at 25° C. to 140° C.

3. The magnetic core according to claim 1, wherein the change rate of the magnetic core loss is -6% to 18% at 25°C to 140°C.

4. The magnetic core according to claim 1, wherein the variation of the magnetic core loss is less than 100 mW / cc at 25°C to 140°C. 5 . The magnetic core according to claim 4 , wherein the variation value of the magnetic core loss is in the range of 60 mW / cc to 99 mW / cc. The magnetic core according to claim 1 , wherein the magnetic core has an initial magnetic permeability of 3000 or more. 7 . The magnetic core according to claim 1 , wherein an atomic ratio of the manganese (Mn) component / the zinc (Zn) component is in the range of 4.40 to 4.

60. 8 . The magnetic core according to claim 1 , wherein the magnetic ion agent comprises a compound (Fe+Co) of iron (Fe) and cobalt (Co). 9 . The magnetic core according to claim 8 , wherein in the magnetic ion agent, an atomic ratio of a compound of iron (Fe) and cobalt (Co) (Fe+Co) is in the range of 2.08 to 2.

10. 10 . The magnetic core according to claim 1 , wherein an atomic ratio of the cobalt (Co) component relative to total atoms of the main component is in the range of 0.005 to 0.

01.

11. The magnetic core of claim 1, wherein the non-magnetic additive comprises at least one of calcium oxide (CaO), niobium oxide (Nb2O5), or a mixture thereof. 12 . The magnetic core according to claim 11 , wherein the content of calcium oxide (CaO) is 400 ppm to 600 ppm.

13. The magnetic core according to claim 11, wherein the content of the niobium oxide (Nb2O5) is 50 ppm to 600 ppm.

14. A magnetic core having the following WD-XRF (wavelength dispersive X-ray fluorescence) analysis results: The weight ratio of manganese oxide (MnO) is 21.2wt% to 21.6wt%; The weight ratio of zinc oxide (ZnO) is 5.7wt% to 6.1wt%; The weight ratio of iron oxide (Fe2O3) is 72wt% to 72.7wt%; The weight ratio of cobalt oxide (Co3O4) is 0.3wt% to 0.4wt%; The calcium oxide (CaO) content is 400 ppm to 600 ppm; and The content of niobium oxide (Nb2O5) is 50 ppm to 600 ppm.